Coronial Processes : An inspection of the arrangements in place in the Police Service of Northern Ireland to manage and disclose information in support of the Coronial process in Northern Ireland.: An inspection of the arrangements in place in the Police Service of Northern Ireland to manage and disclose information in support of the Coronial process in Northern Ireland. (2016) - Northern Ireland., Criminal Justice Inspectorate,
No abstract available